Water Quality and Zooplankton Community Structure of Selected Sites within Chemususu Dam and its Associated Rivers, Baringo County, Kenya - Koromicha, B. C.; Chemoiwa , E. J.; Kipsumbai, P. (Africa Environmental Review Journal, 2022)
The main importance of zooplankton is that they have a crucial role in the food webs of the aquatic ecosystem. However, anthropogenic activities have potential hazardous impact on them. Zooplanktons respond rapidly to physical and chemical fluctuations in the aquatic environment they occupy. The present study determined the spatial and seasonal variation of zooplanktons abundance, distribution and diversity in connection to water quality in Chemususu dam. Sampling was done in six sites, River Sawich (R1) and River Barain (R2), which are the two main inflowing rivers, the dam with three randomly selected stations (D1, D2 and D3) and the dam outlet, river Chemususu (R3). The study was carried out from December 2016 to March 2017 (dry season) and from May to July 2017 (wet season). Standard methods were used to analyze zooplanktons community structure and water samples collected from the dam. The physico-chemical parameters displayed considerable disparity in relation to prevailing conditions with TDS and carbonates showing significant spatial variation, and temperature, total dissolved solids (TDS), total suspended solids (TSS), and salinity indicating a substantial seasonal difference (p<0.05). The analysis of nutrients showed that phosphates, nitrates, and chlorides were not significantly between seasons and among sampling sites, but carbonates were significantly higher in dam sites compared to rivers (p < 0.05). The zooplankton comprised of 45 species, mainly Rotifera accounting for 57.8% to the overall zooplankton abundance, Cladorecans recorded were 24.4%, Copepoda (13.3%) while Ostracoda (4.4%). The principal component analysis (PCA) indicated the first component explained 80.4% of variance with major contributors being TDS, salinity, carbonates and turbidity during the dry season among the rivers, while the second component explains 17.2% of variation with major contribution being TSS and NO3 during the dry and wet seasons. Based on findings, the study recommends researchers to examine trends of water quality over years, identify adaptive features of zooplanktons to food sources, and establish relationship between zooplanktons and phytoplanktons.